The Fornix in Mild Cognitive Impairment and Alzheimer’s Disease - Nowrangi, Milap A.; Rosenberg, Paul B. (Frontiers in Aging Neuroscience, 2015)
The fornix is an integral white matter bundle located in the medial diencephalon and is part of the limbic structures. It serves a vital role in memory functions and as such has become the subject of recent research emphasis in Alzheimer’s disease (AD) and Mild Cognitive Impairment (MCI). As the characteristic pathological processes of AD progress, structural and functional changes to the medial temporal lobes and other regions become evident years before clinical symptoms are present. Though gray matter atrophy has been the most studied, degradation of white matter structures especially the fornix may precede these and has become detectable with use of diffusion tensor imaging (DTI) and other complimentary imaging techniques. Recent research utilizing DTI measurement of the fornix has shown good discriminability of diagnostic groups, particularly early and preclinical, as well as predictive power for incident MCI and AD. Stimulating and modulating fornix function by way of DBS has been an exciting new area as pharmacological therapeutics have been slow to develop.